Discovery of a class of highly potent Janus Kinase 1/2 (JAK1/2) inhibitors demonstrating effective cell-based blockade of IL-13 signaling. Issue 12 (15th June 2019) - Zak, Mark; Hanan, Emily J.; Lupardus, Patrick; Brown, David G.; Robinson, Colin; Siu, Michael; Lyssikatos, Joseph P.; Romero, F. Anthony; Zhao, Guiling; Kellar, Terry; Mendonca, Rohan; Ray, Nicholas C.; et al.
Graphical abstract: Abstract: Disruption of interleukin-13 (IL-13) signaling with large molecule antibody therapies has shown promise in diseases of allergic inflammation. Given that IL-13 recruits several members of the Janus Kinase family (JAK1, JAK2, and TYK2) to its receptor complex, JAK inhibition may offer an alternate small molecule approach to disrupting IL-13 signaling. Herein we demonstrate that JAK1 is likely the isoform most important to IL-13 signaling. Structure-based design was then used to improve the JAK1 potency of a series of previously reported JAK2 inhibitors. The ability to impede IL-13 signaling was thereby significantly improved, with the best compounds exhibiting single digit nM IC50 's in cell-based assays dependent upon IL-13 signaling. Appropriate substitution was further found to influence inhibition of a key off-target, LRRK2. Finally, the most potent compounds were found to be metabolically labile, which makes them ideal scaffolds for further development as topical agents for IL-13 mediated diseases of the lungs and skin (for example asthma and atopic dermatitis, respectively).